Biomaterial-driven regenerative drug delivery: a vicennial bibliometric landscape - Shen, Xin; Deng, Haobin; Lin, Jing; Wang, Jianhua; Liu, Yilun; Mo, Shikun (Frontiers in Medicine, 2025)
IntroductionBiomaterials are increasingly central to innovations in drug delivery and regenerative medicine, driving new therapeutic strategies for chronic diseases and tissue repair. Despite rapid growth, a comprehensive, data-driven overview of this evolving interdisciplinary landscape has been lacking.MethodsHere, we present a bibliometric analysis of articles and reviews published in the Science Citation Index Expanded (Web of Science Core Collection) from January 2005 to December 2024.Results and discussionThe findings present a bibliometric visualization that highlights key trends in publication volume, geographical distribution of research, leading institutions, top journals, research categories, and emerging keywords. Cross-disciplinary integration of biomaterials, regenerative medicine, and drug delivery is accelerating advances in stem cell-based therapies, tissue engineering, and precision drug delivery platforms. Promising frontiers include personalized medicine, organoids, organ-on-chip technologies, and digital modelling of cellular systems. However, significant challenges remain in scalability, safety, and regulatory translation. This work provides a comprehensive reference for navigating current trends and identifying future opportunities in biomaterial-driven regenerative drug delivery.